MULTIPLEX-PCR FOR DETECTION OF Î²-LACTAM RESISTANCE IN Staphylococcus spp. (Revista de Ciência Veterinária e Saúde Pública, 2019)
A Staphylococcus Multiplex PCR system was developed for the simultaneous detection of the mecA, mecC, blaZ (resistance genes of b-lactam resistance) and PVL (pathogenicity factor gene), associated with an internal reaction control with the 16S rRNA gene. There were used primers described in the literature with and without modification and designed primers to standardize the hybridization and amplification temperature of distinct bands with 139 bp (mecC), 228 bp (16S), 313 bp (mecA), 408 bp (PVL) and 516 bp (blaZ) of molecular weight. The standardization was performed in ATCC strains and Staphylococcus schleiferiand tested in 56 strains of Staphylococcusspp. The 16S gene (internal control) was amplified in all samples, mecA gene was detected in two samples, mecA associated with mecC gene in one sample, mecA associated to the blaZ gene in 14 samples and the blaZ gene in 15 samples. No resistance genes were amplified in 24 samples. The PVL gene was not amplified in any of the samples tested.